Pengaruh Dosis Penambahan Biochar Sekam Padi pada Tanah Pasir Terhadap Infiltrasi dan Kemampuan Tanah Menahan Air ( Water Holding Capacity ) - Hartawan, Bagus; Suharyatun, Siti; Amien, Elhamida Rezkia; Tusi, Ahmad (Jurnal Agricultural Biosystem Engineering, 2026)
Sandy soil is characterized by a high infiltration rate and low water retention capacity, making it less effective in supplying water for plant growth. This study aimed to analyze the effect of rice husk biochar application on infiltration and water retention capacity in sandy soil. The experiment was conducted from July to August 2024 at the Greenhouse of the Department of Agricultural Engineering, Faculty of Agriculture, University of Lampung. Four treatments were applied: A1 (0% biochar), A2 (10%), A3 (15%), and A4 (20%), each replicated three times. Observed parameters included soil moisture content, infiltration rate, water holding capacity, and the duration of water content change. Results indicated that rice husk biochar addition reduced the infiltration rate of sandy soil, with the lowest value observed in A4 (20%) at 6.42 mm/hour compared to the control A1 (0%) at 7.89 mm/hour. The time required for soil moisture to decrease from 14% to 8% was shortest in A1 (96 hours) and longest in A4 (456 hours). It can be concluded that rice husk biochar enhances the water retention ability of sandy soil and slows down moisture loss, with the 20% dose being the most effective treatment in improving water holding capacity.